Farm boys : lives of gay men from the rural Midwest - Fellows, Will (UPCC book collections on Project MUSE., 1996)
Homosexuality is often seen as a purely urban experience, far removed from rural and small-town life. Farm Boys undermines that cliche by telling the stories of more than three dozen gay men, ranging in age from 24 to 84, who grew up in farm families in the midwestern United States. These men speak of the ways their farm upbringings influenced the course and character of their lives, especially with regard to gender identity and sexual orientation. Whether painful, funny, or matter-of-fact, their plain-spoken accounts will move and educate any reader, gay or not, from farm or city.